IMAGE OF THE WORLD AND DEVALUATION OF MORAL VALUES: ASPECTS OF THE PROBLEM - Yuri V. Kolin (International Journal of Innovative Technologies in Social Science, 2022)
The article analyzes the dangers of scientific and technological progress for society, it is argued that the relativization of moral values in modern society has its source in relation to man as an object, which leads to primitivization and disintegration of the individual. The attitude to another culture as an object for colonization also contributes to the moral degradation of society. The article draws a distinction between a moral and a civilized person, criticizes the theoretical foundations of the concepts of posthumanism, transhumanism, radical constructivism and constructive alternativeism from the standpoint of the concept of moral values as a manifestation of the substantiality of the individual and mass consciousness in general. The moral sphere is considered in the article as a manifestation of the substantiality of human consciousness, the image of the world based on the relationship to the Other as a subject. The article discusses the process of formation of the moral sphere of society as the basis of the image of the world, a manifestation of the substantiality of human consciousness, its irreducibility to schemes and attitudes imposed within the framework of private interests. As examples of the attitude to moral values as a criterion of the substantiality of human consciousness, the legend of the Grand Inquisitor in the novel by F. Dostoevsky "The Brothers Karamazov", the understanding of humanitarian values in the novel by Yu. Dombrovsky "Faculty of unnecessary things", as well as the concept of the categorical imperative by I. Kant are given.